2022
DOI: 10.1097/md.0000000000029837
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal cocoon syndrome: Rare cause of intestinal obstruction—Case report and systematic review of literature

Abstract: Background: Abdominal cocoon or sclerosing encapsulating peritonitis is an uncommon condition in which the small bowel is completely or partially encased by a thick fibrotic membrane. Our study presents a case of sclerosing encapsulating peritonitis and conducts a literature review.Methods: A bibliographic research was conducted. Our research comprised 97 articles. Gender, age, symptoms, diagnostic procedures, and treatment were all included in the database of patient characteristics.Case presentation: A 51-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…In our case, the patient presented with intestinal obstruction and acute abdomen in the same way as some previously reported cases [10,11]. The histopathological findings of a thickening of the fibroconnective tissue of the peritoneum, acute and chronic inflammatory infiltrates, lymphatic dilation without evidence of foreign body granulomas, giant cells, or birefringent material give the definitive diagnosis.…”
Section: Discussionsupporting
confidence: 72%
“…In our case, the patient presented with intestinal obstruction and acute abdomen in the same way as some previously reported cases [10,11]. The histopathological findings of a thickening of the fibroconnective tissue of the peritoneum, acute and chronic inflammatory infiltrates, lymphatic dilation without evidence of foreign body granulomas, giant cells, or birefringent material give the definitive diagnosis.…”
Section: Discussionsupporting
confidence: 72%
“…Abdominal cocoon syndrome is rare and characterized by total or partial encapsulation of abdominal organs by dense fibrous adhesions. 13,14 This syndrome most often involves the intestinal tract, presenting with signs and symptoms of obstruction. The etiology is poorly understood, but secondary forms have been described in the setting of intrabdominal inflammation, autoimmune disease, and following abdominal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Chorti et al. conducted a systematic review of 240 reported cases of ACS and showed that the most common symptoms include diffuse abdominal pain and bowel obstruction symptomatology 3 . Furthermore, contrast‐enhanced abdominal CT scan was significantly correlated with preoperative diagnosis of ACS which was performed in 43% of patients, and surgical management was the most common treatment for ACS cases.…”
Section: Discussionmentioning
confidence: 99%
“…This syndrome is more common in tropical and subtropical countries and is predominant in the male population 2 . The clinical manifestations are not specific and preoperative diagnosis is difficult; therefore, nearly 70% of the patients are diagnosed intraoperatively 3 . EPS can be idiopathic or secondary to a wide range of underlying causes.…”
Section: Introductionmentioning
confidence: 99%